1997
DOI: 10.1111/j.1547-5069.1997.tb01139.x
|View full text |Cite
|
Sign up to set email alerts
|

National Delphi Study to Determine Competencies for Nursing Leadership in Public Health

Abstract: Graduate schools in nursing and public health must prepare students with broad-based competencies from a variety of disciplines. Findings of this national survey provide a database for curriculum development and evaluation of programs to prepare nurse leaders for roles in public health-based delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Historically, strong management skills have been valued more than strong leadership skills in the healthcare industry. Although greater emphasis has been placed on leadership skills in management in the last decade, research by Misener et al (1997) suggests that leadership may continue to be undervalued in nursing curricula and that internalization of the value of leadership in nursing should be increased. At a local level, leaders are slowly starting to move away from their previous administrative/controller roles to as supportive coaches to staff (Chapman 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, strong management skills have been valued more than strong leadership skills in the healthcare industry. Although greater emphasis has been placed on leadership skills in management in the last decade, research by Misener et al (1997) suggests that leadership may continue to be undervalued in nursing curricula and that internalization of the value of leadership in nursing should be increased. At a local level, leaders are slowly starting to move away from their previous administrative/controller roles to as supportive coaches to staff (Chapman 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Engaging students in policy content has been stated perhaps most strongly by Cohen and associates (1996) who indicated that "Every graduate of a doctoral program in nursing should be able to articulate the policy relevance of his or her research" (p. 265, 1996). Although some research has been conducted focusing on health policy content in nursing education programs (Andreoli, Musser, & Otto, 1987) and the identification of specific political competencies for specialty practice (Misener et al, 1997), few researchers query nurses who have provided leadership in the policy arena to better understand the nature of policy work and strategies that may facilitate increased participation.…”
mentioning
confidence: 99%
“…Similar to George's () early work describing staff PHNs' concept of leadership, DONs in our study identified attributes of effective leadership that encompassed influence/persuasion, role modeling, and mentorship. DONs also articulated the need to develop political competency, program leadership, and management capabilities reflective of work conducted by Misener and colleagues ().…”
Section: Discussionmentioning
confidence: 99%